Student Preferences and Socio-Cultural Transformations of Professional Groups - Sobkin, V.S.; Kalashnikova, E.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2020)
Objectives. To characterize the preferences of modern adolescents in professional fields, taking into account the influence of demographic and socio-stratification factors, and also to identify the influence of socio-cultural factors: social success (class status, academic performance) and components of a life position (emotional assessment of prospects, plans, value orientations) on the transformation of ideas schoolchildren about professional fields and the features of their recruitment into various professional groups. Background. In connection with the complexity of the current sociocultural situation, which determines the uniqueness of the socialization of the modern adolescent (value-normative uncertainty, increasing social inequality, changing the information space, the transformation of the main social institutions of socialization, primarily family and school), it is becoming important to pay attention to the peculiarities of modern youth in various professional fields. Study design. The study examined the frequency of students’ choice of various professional fields for further activities. The influence of demographic, socio-stratification, factors of social success, components of the life position of students was studied. Participants. 11803 students of the 7th, 9th and 11th grades. Measurements. Anonymous questionnaire survey of students in primary and senior schools, using closed-ended questions, StatSoftStatistika 6.0 package (significant differences, factor analysis). Results. The features of the influence of demographic and socio-stratification factors on the professional preferences of modern adolescents are revealed. Using the factor analysis procedure, five generalized characteristics of the life position of schoolchildren are identified that determine the characteristics of their orientations towards different types of professional activity. Conclusions. The data obtained make it possible to predict the influence of demographic, socio-stratification and sociocultural factors on the nature of the transformations of various socio-professional groups. Цель. Охарактеризовать предпочтения современных подростков в профессиональных сферах с учетом влияния демографических и социально-стратификационных факторов, а также выявить влияние социокультурных факторов — социальной успешности (статус в классе, успеваемость) и компонентов жизненной позиции (эмоциональная оценка перспектив, планы, ценностные ориентации) — на трансформацию представлений школьников о профессиональных сферах и особенности их рекрутирования в различные профессиональные группы. Контекст и актуальность. В связи со сложностью современной социокультурной ситуации, определяющей своеобразие социализации современного подростка (ценностно-нормативная неопределенность, усиление социального неравенства, изменение информационного пространства, трансформация основных социальных институтов социализации, в первую очередь, семьи и школы), сегодня становится важным обратить внимание на особенности рекрутирования современной молодежи в различные профессиональные сферы. Дизайн исследования. В работе изучалась частотность выбора учащимися различных профессиональных сфер для дальнейшей деятельности. Исследовались влияние демографических, социально-стратификационных факторов социальной успешности, компонентов жизненной позиции школьников. Участники. 11803 учащихся 7-х, 9-х и 11-х классов. Методы (инструменты). Анонимный анкетный опрос учащихся основной и старшей школы с использованием закрытых вопросов, пакет StatSoftStatistika 6.0. (значимые различия, факторный анализ). Результаты. Выявлены особенности влияния демографических и социально-стратификационных факторов на профессиональные предпочтения современных подростков. С помощью процедуры факторного анализа выделены пять обобщенных характеристик жизненной позиции школьников, которые определяют особенности их ориентаций на разные виды профессиональной деятельности. Основные выводы. Полученные данные дают возможность спрогнозировать влияние демографических, социально-стратификационных и социокультурных факторов на характер трансформаций различных социально-профессиональных групп.